Inducing moods with background music. (1st January 2012) - van der Zwaag, Marjolein D.; Westerink, Joyce H.D.M.
Music is listened to in many places at many different times. An important aspect of music when played as primary activity is its ability to direct mood. This is beneficial as moods influence several cognitive functions. In this study, we investigated whether and to what extent background music mood induction results in similar mood and physiological patterns to music mood induction as a primary activity. Thirty participants took part in two experimental sessions in which they listened to individually selected music (happy, sad, or no music) and performed an activity (Sudoku or nothing) in a within-subject design. The results showed that mood ratings of valence and energy, skin conductance level, and zygomaticus major facial muscle tension responded best and in similar ways to both types of music mood induction. All in all, the present study showed that moods can be induced when played in the background to an activity. This study therefore shows the potential for systems which select background music that is tuned to direct mood towards a desired state and which can benefit cognitive functioning.